“Using the Statistical Analysis for deduction the childhood status in Iraq during 2006-2010” - علي عمر عبد المحسن; سلمان فائز حامد (Journal of Economics and Administrative Sciences, 2012)
To deduct the childhood status in Iraq, it was important manner to use statistical tools and approaches concerned with interpreting the causal relationships and their attitudes and use classification method for the important effects (variables) to draw an obvious picture of the phenomena under study in order to make it useful through investing, updating and improving it in by demographic studies in the future. Two statistical methods had been used in the field of analyzing data of multivariate analysis namely, Cluster Analysis and Factor Analysis. The present study focuses on four fundamental axes .The nutrition axis, health axis, Educational axis, and the social axis. The study has calculated the indicators of these four axes relying on real data of a sample whose size is (18144) families obtained from the Ministry of planning and Development Cooperation/Central Bureau of statistics and Information Technology Data. The Data has been analyzed by the statistical program (SPSS VERSION 12.0). In the light of the results of the data analysis some conclusions are worth observing: • The conclusions showed that 840 of the Iraqi children whose age is under five years suffer from the medium or server weight, and that fifth of the children undergo from being pygmy (their length does not suit their age). • The conclusions also showed that the majority of death cases of the children under five years 85% occur in infants only.